PENGGUNAAN MEDIA DALAM PEMBELAJARN FIQH PADA DAYAH TRADISIONAL DI ACEH - Ismail Anshari; Tihalimah Tihalimah (Jurnal MUDARRISUNA: Media Kajian Pendidikan Agama Islam, 2019)
Traditional Dayah education in Aceh which has historically contributed to providing resplendent output, but is now starting to face serious challenges that lead to suboptimal quality of education. The study of fiqh in traditional dayahs that have produced quality graduates began to decline. Data collected through observation, interviews, and documentation analyzed through a qualitative approach show some significant findings. First, traditional dayahs in Aceh in fiqh learning have adopted the curriculum of the Aceh Dayah Education Office. Second, the integration of instructional media in the teaching of fiqh in traditional dayahs in Aceh has not been able to improve the quality of fiqh learning. Thirteen, the continuity of innovation in the integration of instructional media in fiqh learning is greatly influenced by internal and external support so that continuous and comprehensive innovation becomes a necessity so that the maximum output produced. This paper suggests a transformation in fiqh learning in traditional dayahs by actualizing learning oriented to the mastery of the material through the integration of learning media.